2009
DOI: 10.1096/fj.09-132795
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial glutathione peroxidase 4 disruption causes male infertility

Abstract: Selenium is linked to male fertility. Glutathione peroxidase 4 (GPx4), first described as an antioxidant enzyme, is the predominant selenoenzyme in testis and has been suspected of being vital for spermatogenesis. Cytosolic, mitochondrial, and nuclear isoforms are all encoded by the same gene. While disruption of entire GPx4 causes early embryonic lethality in mice, inactivation of nuclear GPx4 does not impair embryonic development or fertility. Here, we show that deletion of mitochondrial GPx4 (mGPx4) allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
197
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(214 citation statements)
references
References 36 publications
(46 reference statements)
6
197
2
3
Order By: Relevance
“…These results suggest that mitochondrial dysfunction in spermatozoa is a major functional defect brought on by GPx4 deficiency. During submission of the manuscript for this report, Conrad and his colleagues demonstrated that depletion of mitochondrial GPx4 causes impaired sperm quality, severe structural abnormalities, and male infertility (35), which also confirms our ideas.…”
Section: Discussionsupporting
confidence: 84%
“…These results suggest that mitochondrial dysfunction in spermatozoa is a major functional defect brought on by GPx4 deficiency. During submission of the manuscript for this report, Conrad and his colleagues demonstrated that depletion of mitochondrial GPx4 causes impaired sperm quality, severe structural abnormalities, and male infertility (35), which also confirms our ideas.…”
Section: Discussionsupporting
confidence: 84%
“…IVF experiments were performed as described previously (25). Sperm quality was measured using an IVOS Sperm Analyzer (version 12.1c; Hamilton Research) as previously described (26). The motility (percentage of all motile spermatozoa) and progressivity (percentage of spermatozoa with a minimum velocity of Ն60 m/second and straightness of Ն50%) were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…45 Such programs have revealed many critical genes for human diseases, including male infertility. [46][47][48][49] …”
Section: Mouse Models In Male Fertility Research D Jamsai and Mk O'brmentioning
confidence: 99%